2019
DOI: 10.3389/fcvm.2019.00103
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of 4D-Flow MRI Derived Mitral Regurgitation Quantification Methods

Abstract: Background: Four-dimensional flow cardiac magnetic resonance (4D flow CMR) is an emerging non-invasive imaging technology that can be used to quantify mitral regurgitation (MR) volume. Current methods of quantification have demonstrated limitations in accurate analysis, particularly in difficult cases such as complex congenital heart disease. 4D flow CMR methods aim to circumvent these limitations and allow accurate quantification of MR volume even in complex cases. This systematic review aims to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 27 publications
0
33
0
1
Order By: Relevance
“…These patients should receive more attention in clinical disease management and treatment. However, according to the current guidelines for evaluating the degree of mitral regurgitation, there is a lack of true gold standard, which method quantifies MR severity with the highest degree of accuracy and reliability is unknown 16 , the accuracy of this semi-quantitative evaluation of regurgitation severity needs further study, the 4D-flow, which produces a direct quantification of MR by quantifying flow directly at the valve and is valid in the presence of multiple valve lesions or shunt flow 34 , to investigate the clinical benefit in quantification regurgitation are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…These patients should receive more attention in clinical disease management and treatment. However, according to the current guidelines for evaluating the degree of mitral regurgitation, there is a lack of true gold standard, which method quantifies MR severity with the highest degree of accuracy and reliability is unknown 16 , the accuracy of this semi-quantitative evaluation of regurgitation severity needs further study, the 4D-flow, which produces a direct quantification of MR by quantifying flow directly at the valve and is valid in the presence of multiple valve lesions or shunt flow 34 , to investigate the clinical benefit in quantification regurgitation are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Direct quantification of the regurgitant jet is particularly useful in pathologies involving multiple valves. A systematic review of 4D flow-derived methods for MR quantification identified seven studies that demonstrated that 4D flowderived MR volume is similar to that derived using standard CMR methods and even to that derived using 3D transoesophageal echocardiography (TOE) methods 29 . In one study, a standard CMR method for quantification of MR volume and 4D flow-derived methods yielded similar results 30 .…”
Section: Cine Imagesmentioning
confidence: 99%
“…15,24,25 CMR can also assess the impact of systolic variation on mitral cardiography. 46 In one retrospective study, as compared to multiplanar standard techniques for CMR, 4D flow methods had excellent correlation with high inter-and intra-observer reliability. 47…”
Section: Ta B L E 2 Possible Methods To Calculate Mitral Regurgitatiomentioning
confidence: 94%
“…A systematic review of seven studies with 4D flow‐derived methods for MR quantification demonstrates increased accuracy and reliability in direct measurement when compared to standard CMR techniques and establishes a complementary role with echocardiography. 46 In one retrospective study, as compared to multiplanar standard techniques for CMR, 4D flow methods had excellent correlation with high inter‐ and intra‐observer reliability. 47 …”
Section: Imaging Protocols and Methodology For Assessment Of Mr Via Cmrmentioning
confidence: 98%